Ionic liquids as viscosity modifiers for heavy and extra-heavy crude oils. (1st March 2015) - Subramanian, Deepa; Wu, Kathleen; Firoozabadi, Abbas
Graphical abstract: Highlights: Ionic liquids are used to reduce the viscosity of heavy oil and bitumens. Viscosity reduction up to 35% is observed using 5 ppm of dodecylpyridinium chloride. Ionic liquids seem to interact with asphaltenes to decrease their aggregate size. Decrease in asphaltene aggregate size seems to lower the crude viscosity. Intermolecular interactions include π – π, aliphatic, acid–base, and charge-transfer. Abstract: Heavy oils and extra-heavy oils (bitumens) are difficult to produce and transport due to problems associated with the aggregation of asphaltene molecules. Asphaltenes, a primary component of heavy oils and bitumens, affect the viscosity significantly. Traditional methods of viscosity reduction for heavy petroleum fluids include thermal or dilution methods. In this work, we employ an alternative method for viscosity reduction, by using functionalized molecules that could interact with the asphaltenes and change the properties of the crude oil at the molecular level, reducing viscosity. Ionic liquids, having favorable thermophysical properties such as low vapor pressure, are the functionalized molecules tested in this work. Various properties of the ionic liquids such as alkyl tail lengths (C2, C4, C6, C8, C10, and C12), counter-ion charge density (chloride, thiocyanate, and tetrafluoroborate), and type of head group (imidazolium, pyridinium, and thiazolium) are tested with a Mexican heavy oil and Canadian and Venezuelan bitumens. Small amounts of the additives (between 1 and 10 ppm), dissolved in toluene, are used. Viscosity reduction up to 35% is observed for the crude oils, with dodecylpyridinium chloride showing the maximum reduction. Various molecular interactions between the ionic liquids and the asphaltene molecules, such as aromatic, acid–base, and charge-transfer interactions, seem to hinder the asphaltene aggregate formation, which consequently reduces the viscosity. These results set the stage for further research on the viscosity reduction of heavy oil and extra-heavy oils by using functionalized molecules.